mRNA vaccines: a new opportunity for malaria, tuberculosis and HIV - Matarazzo, Laura; Bettencourt, Paulo J. G. (Frontiers in Immunology, 2023)
The success of the first licensed mRNA-based vaccines against COVID-19 has created a widespread interest on mRNA technology for vaccinology. As expected, the number of mRNA vaccines in preclinical and clinical development increased exponentially since 2020, including numerous improvements in mRNA formulation design, delivery methods and manufacturing processes. However, the technology faces challenges such as the cost of raw materials, the lack of standardization, and delivery optimization. MRNA technology may provide a solution to some of the emerging infectious diseases as well as the deadliest hard-to-treat infectious diseases malaria, tuberculosis, and human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS), for which an effective vaccine, easily deployable to endemic areas is urgently needed. In this review, we discuss the functional structure, design, manufacturing processes and delivery methods of mRNA vaccines. We provide an up-to-date overview of the preclinical and clinical development of mRNA vaccines against infectious diseases, and discuss the immunogenicity, efficacy and correlates of protection of mRNA vaccines, with particular focus on research and development of mRNA vaccines against malaria, tuberculosis and HIV.